The primary education for disadvantaged children = (The World Bank in Vietnam (WB), 2003)
The objective of the Primary Education for Disadvantaged Children Project for Vietnam is to improve access to primary school and the quality of education for disadvantaged boys and girls. The reallocation of the credit proceeds will finance the costs associated with continuing activities currently financed by the Multi-Donor Trust Fund (MDTF) and enhance the impact of these well-performing components of the project. In particular, the International Development Association (IDA) funds will enable the continuing delivery of a package of support for primary education in order to ensure a Fundamental School Quality Level (FSQL) is reached at all main and satellite schools in 226 districts in the Project's 40 target provinces. This extension of existing activities for a further year in the project districts can be expected to contribute to increasing primary education enrollment and completion and to improving learning achievement in disadvantaged communities, as well as for specific highly vulnerable groups such as children living with a disability. Further, the changes will allow full transfer of the project's innovative interventions into day-to-day Government processes and procedures, allow for nation-wide expansion and implementation, facilitate a smooth transition and ensure full sustainability in the long term